CONTROLLER AND METHOD TO MEDIATE DATA COLLECTION FROM SMART SENSORS FOR FAB APPLICATIONS - LEV-AMI, UZI; SIFNATSCH, GUENTER; ATTWOOD, MARK (2005)
The present invention relates to control of and data collection from sensors associated with tools. In particular, it relates to using a controller to mediate communications among a tool, sensors associated with the tool and data users, such as a host system or distributed processors. Particular aspects of the present invention are described in the claims, specification and drawings. La présente invention concerne la gestion et la collecte de données à partir de capteur associés à des outils. Elle permet en particulier d'induire des communications entre un outil, des capteurs associés à cet outil et des utilisateurs, tels qu'un système hôte ou des processeurs distribués. Des aspects particuliers de l'invention sont décrits dans les revendications, spécifications et figures.